Does Perceived Stress Affect the Relationship between Personality and Sports Enjoyment? - Dunker, Freya; Freund, Philipp A.; Engels, Eliane (European Journal of Health Psychology, 2020)
Background: Sports enjoyment is a prerequisite for continued engagement in sports (e.g., Mullen et al., 2011; Woods, Tannehill, & Walsh, 2012). To date, it is understudied whether perceived stress and personality relate to the experience of sports enjoyment. Aim: The aim of the present study was to investigate the relationships between perceived stress, personality (the Big Five), and sports enjoyment. Method: Data were collected online from a group of N = 195 adults. There were two points of measurements with an interval of 4 weeks in between. Personality was assessed at t1, while perceived stress and sports enjoyment were measured at t2. Results: The results indicate that perceived stress is significantly related to sports enjoyment: A high amount of perceived stress was associated with less enjoyment of sports. Neuroticism, extraversion, conscientiousness, and agreeableness were related to sports enjoyment, but openness was not. Models testing the mediating effect of perceived stress for personality on sports enjoyment showed significant direct effects for extraversion and conscientiousness and significant indirect effects for neuroticism, extraversion, and conscientiousness. Limitations: Limitations concerning the sample characteristics and some poor fit statistics for the models including openness and extraversion are discussed. Conclusion: Overall, our findings suggest that perceived stress influences the affective experience in physical exercise.
Created from Fastlane, Scopus look-up
Keywords: Big Five; health; perceived stress; personality; sports enjoyment